Performance Analysis of Code-Based Relative GPS Positioning as Function of Baseline Separation - Carvalho, Gustavo; Silva Filho, Felipe; Menezes Filho, Rogério; Pereira, Victor Hugo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2020)
With the beginning of the space age and, consequently, the advent of new technologies, it was possible to develop low-cost positioning and navigation systems with global coverage, reaching accuracy up to 10 m. Nevertheless, many modern-day applications have arisen demanding navigation technologies able to provide sub-meter position accuracy, still at low-cost. Relative Global Navigation Satellite System (RGNSS) is a well-known technique used to correct common-mode errors present in GNSS observables. RGNSS is susceptible to two main degradation factors, namely, communication latency and baseline separation between the rover and reference. This paper investigates the sensitivity of position estimation accuracy as function of baseline separation between stationary Global Positioning System (GPS) receivers. As main contribution, we show that it is possible to achieve 1 m horizontal accuracy at 68% of probability with baselines up to 2100 km between rover and reference station. Experimental data collected from the Brazilian Network for Continuous Monitoring of GNSS (RBMC) are used to validate the analysis.